Procedimentos discursivos na fala e na escrita de Itabaiana/SE: estratégias de evidencialidade/modalização oracionais de primeira pessoa do singular - Peixoto, Jackeline Carvalho; Freitag, Raquel M. Ko. (Scientia Plena, 2011)
Based on North American Functionalism and Variacionist Sociolinguistics theoretical assumptions we analyzed clausal modalization/evidential strategies of 1st singular person – specify “acho que” – in Itabaiana’s spoken and written language. In a quantitative approach data collected from GELINS data bank are analyzed. We conclude that “acho que” construction is in grammaticalization process: increased by frequency of use the construction takes on new semantic and functional features, becomes as opinion marker and a doubt marker.